2021
DOI: 10.1039/d1cy01016f
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of the Lindlar catalyst in alkyne semi-hydrogenation: a direct liquid-phase adsorption study

Abstract: We study the alkyne semi-hydrogenation selectivity over Pd and Lindlar catalyst with liquid-phase adsorption. The results indicate that there are strongly-adsorbing alkyne and alkene sites; alkenes react non-selectively over the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 80 publications
0
18
0
2
Order By: Relevance
“…Table 2 lists the adsorption energy of the modifiers calculated in this study and that of MBE reported in the previous study. 8 The adsorption energy of MBE is reported to be similar to MBY on Pd(110) and Pd(210) indicating that adsorption of MBE is equally likely over these surfaces opening the possibility for MBE adsorption and subsequent reactions. Note that the adsorption structure of MBE (adsorbed via H atom, OH group, or CH 3 group) little changed the adsorption energy.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 93%
See 3 more Smart Citations
“…Table 2 lists the adsorption energy of the modifiers calculated in this study and that of MBE reported in the previous study. 8 The adsorption energy of MBE is reported to be similar to MBY on Pd(110) and Pd(210) indicating that adsorption of MBE is equally likely over these surfaces opening the possibility for MBE adsorption and subsequent reactions. Note that the adsorption structure of MBE (adsorbed via H atom, OH group, or CH 3 group) little changed the adsorption energy.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 93%
“…Oligomerization is a major side-reaction in the case reaction with neat alkyne 17 or reaction in gas-phase 23 but negligible with isopropanol solvent. 8 We have previously developed flow reactor systems equipped with in-line GC 24 and HPLC 29 that take aliquots from the reactor outlet and directly inject them into the chromatography columns (note that in a strict classification, 30 they are called at-line analysis). Such technic minimizes human operation and enables automated feedback to the design of experiment algorithms.…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
See 2 more Smart Citations
“…At present, palladium-catalyzed reactions can be considered as the most abundant in fine chemistry, which makes palladium catalysts extremely important [1][2][3][4][5][6][7]. Recently, there has been increased interest in environmentally benign Pd-catalyzed processes that are also economically viable.…”
Section: Introductionmentioning
confidence: 99%